Pengaruh Insentif dan Gaya Kepemimpinan terhadap Kinerja Karyawan di Perguruan Tinggi Universitas Muhammadiyah Ponorogo - La Harjono; Catur Wulandari; Yuyun Iriani; Sarlin Sarlin (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the effect of incentives and leadership style on employee performance in a college environment, especially at Muhammadiyah University of Ponorogo. The approach used is a survey approach with a quantitative method. This type of research is associative in nature which aims to test the relationship between incentive variables, leadership style, and employee performance. The population in this study was 130 employees, with a purposive sampling technique that produced 100 respondents as a sample. The data collection instrument used a Likert scale and was analyzed by t-test and simultaneous test. The results of the study showed that incentives had a significant partial effect on employee performance (t count = 5.810> t table = 2.052; sig. 0.00 <0.05), while leadership style did not have a significant partial effect (t count = 1.865 <t table = 2.052; sig. 0.065> 0.05). However, simultaneously, incentives and leadership style had a significant effect on employee performance. the results of the reliability test show a cronbach's alpha value > 0.6, which indicates that the research instrument is reliable. This study emphasizes the importance of a combination of appropriate incentives and appropriate leadership styles in improving employee performance in higher education institutions.